Parenting Style as Determinant of Toddler Nutritional Status - Reny Mareta Sari; Sergiana F. Saba Jawa (Universitas STRADA Indonesia, 2025)
Appropriate nutrition is essential during the growth and development of toddlers. Therefore, feeding patterns, as a form of parenting style, play an important role in determining the nutritional status of toddlers. This study aims to analyze the relationship between parenting styles and the nutritional status of toddlers in one of the Community heath posts (Posyandu) in Kediri City. The research was conducted toward 56 respondents. The measurement of parenting style was conducted to the mother using questionnaire while nutritional status was measured using health card (KMS). The result of study showed that most of the mothers are having good parenting style (51,8%) and most of the toddlers are having normal nutritional status (71,4%). Statistical analysis conducted using Chi-Square showed that there is significant relationship between parenting style and toddlers’ nutritional status (p-value = 0,027). Therefore, appropriate feeding pattern and parenting style should be applied to all parents to make sure all children are having good nutritional status for their growth and development.